Naftifine hydrochloride (NH) in the treatment of pityriasis versicolor - L. P. Kotrekhova; A. A. Vashkevich; E. N. Tsurupa; P. A. Reztsova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Introduction & objectives: The purpose of this study was to demonstrate the efficacy comparability of 1% NH lotion vs. of 1% NH cream (exoderil, Sandoz) in the treatment of pityriasis versicolor. Material & methods. 71 patients with pityriasis versicolor were randomly allocated either to receive NH lotion once daily (NH lotion group (п = 35, 38.6 years (95% CI [33,7, 43.5]) or NH cream once daily (NH cream group (п = 36, 40.8 years (95% CI [36,6, 45.0]) for 14 days. Mycological evaluations (microscopy and culture) were performed at weeks 2 and 3, inflammation symptoms evaluations were scored at day 3, weeks 2 and 3 after start of the therapy. Overall cure rates assessment included results of mycological, clinical outcomes and safety evaluation. Results. There was no difference between groups in mycological cure rates (94% vs 92%) and inflammation regression (97% vs 97%). Overall cure rate was 91% and 92% of patients in NH lotion and NH cream groups respectively (p = 0,97). Conclusion. 1% NH lotion and 1% NH cream are effective in the treatment of pityriasis versicolor.